2023
DOI: 10.3390/su15075814
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Virtual Reality in Climate Change Education Increases with Amount of Body Movement and Message Specificity

Abstract: Climate change impacts are felt globally, and the impacts are increasing in severity and intensity. Developing new interventions to encourage behaviors that address climate change is crucial. This pre-registered field study investigated how the design of a virtual reality (VR) experience about ocean acidification could impact participants’ learning, behavior, and perceptions about climate change through the manipulation of the experience message framing, the sex of voice-over and the pace of the experience, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 100 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…This combination provides a unique and immersive learning experience, fostering students' CT skills. Climate change VR videos offer a realistic and interactive environment, allowing students to experience the consequences of climate change firsthand, as the experience of previous studies (Queiroz et al, 2023). This immersive experience triggers students' curiosity and prompts them to identify problems and potential solutions (Thoma et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…This combination provides a unique and immersive learning experience, fostering students' CT skills. Climate change VR videos offer a realistic and interactive environment, allowing students to experience the consequences of climate change firsthand, as the experience of previous studies (Queiroz et al, 2023). This immersive experience triggers students' curiosity and prompts them to identify problems and potential solutions (Thoma et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The positive response from participants highlighted the potential of VR simulations as tools to bridge the gap between scientific understanding, public engagement, and informed decision-making in the frame of sustainable development under conditions of a changing climate. In this regard, some pivotal studies suggested that utilizing immersive VR simulating long-term hazardous processes (e.g., sea level rise) that are often overlooked by the general public could provide an alternative approach to increase public awareness concerning the impacts of climate change [85][86][87].…”
Section: Virtual Reality and Geohazardsmentioning
confidence: 99%
“…The descriptive statistics of our systematic review show that VR technology is mostly used in the field of environmental education. Queiroz et al [46] underlined the potential of VR in fostering knowledge gains and self-efficacy in learning. Indeed, Immersive environments such as VR and metaverses are now broadly used in the field of education and training [32].…”
Section: State Of the Art Of Digital Tools For Fostering Environmenta...mentioning
confidence: 99%
“…Interactive multimedia becomes the right strategy to deliver information in an effort to build awareness against animal exploitation in environmental conservation education for children's. [46] Virtual reality Students learning and climate change behavior.…”
mentioning
confidence: 99%